ISTIKHDAMU WASAILI AT TAWASHUL AL IJTIMA’I FII TA’ALLUMI AL LUGHAH AL ARABIYAH MA’A NAMUDZAJ AT TA’ALLUM AL MUDAMMAJ - Azisi; Nurfaiza; Vina Rohmatul Umma (Program Studi Pendidikan Bahasa Arab, 2023)
Limited face-to-face meetings are a new phase in learning Arabic after the number of victims of COVID-19. The blended learning model that integrates face-to-face learning with online learning becomes a learning model that is applied in schools. To assist teachers in maximizing students' Arabic learning outcomes, the use of social media is the most recommended alternative media. The purpose of this article is to describe the use of social media in learning Arabic with a blended learning model and its advantages and disadvantages in learning. This article is included in qualitative research with the type of literature review that produces descriptive data regarding the use of social media in learning Arabic with a blended learning model. This study explains that various social media applications can be developed to learn Arabic. Social media encourages students' interest in learning Arabic through its refreshing display and features. Its easy and practical use makes learning can be done from anywhere and anytime so that the objectives of learning Arabic will be achieved.